2012
DOI: 10.1002/lary.23387
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, quality of life, and functional outcomes of 176 hypopharyngeal cancer patients treated by (Chemo)radiation: The impact of treatment modality and radiation technique

Abstract: Compared to radiotherapy alone, chemoradiation significantly improved functional outcome, increased acute toxicity, but without significant increase in late radiation-induced side effects. Statistically significant deterioration in QoL scores was reported only for xerostomia. IMRT, compared to 3DCRT, reduced the incidence and severity of acute and late toxicity, thereby broadening the therapeutic window, and may allow dose escalation for further improvement of outcomes of laryngeal preservation protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 10 publications
5
34
1
1
Order By: Relevance
“…The authors found that median os was improved in the ccrt group, reported a 2-year ledfs of 31.7% for the ccrt group, and concluded that there was "benefit" with the addition of ccrt for selected patients. Al-Mamgani et al 18 reported on 176 sequential patients treated with either ccrt (n = 104) or rt (n = 74). Patients with more extensive disease and those who were younger and healthier, with a better performance status, were the ones who received ccrt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that median os was improved in the ccrt group, reported a 2-year ledfs of 31.7% for the ccrt group, and concluded that there was "benefit" with the addition of ccrt for selected patients. Al-Mamgani et al 18 reported on 176 sequential patients treated with either ccrt (n = 104) or rt (n = 74). Patients with more extensive disease and those who were younger and healthier, with a better performance status, were the ones who received ccrt.…”
Section: Discussionmentioning
confidence: 99%
“…As oncologists have moved more toward the concept of organ preservation, other treatments have included induction chemoradiotherapy 3,14,15 and transoral laser surgery 16,17 . There is also considerable parallel evidence that the addition of chemotherapy to rt increases acute and late toxicity [18][19][20][21][22] , creating clinical problems that can be particularly severe in this patient population 21 . A complete review of treatment options published by Takes et al 23 concluded that more evidence was needed to determine optimal treatment and that "treatments should be individualized by knowledgeable multidisciplinary teams.…”
Section: Introductionmentioning
confidence: 99%
“…However, RT often results in permanent xerostomia (loss of saliva production). Xerostomia impairs speaking and/or swallowing, increases the risk of dental caries, osteonecrosis of the mandible and malnutrition, and decreases patients’ quality of life 1 . Further, significant oral and pharyngeal mucositis develops during RT of HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…The Meta-Analysis of Chemotherapy in Head and Neck Cancer collaborative group, in a subgroup analysis of 2767 hpc patients, found a 5-year absolute survival improvement of 4% associated with concomitant chemotherapy (hazard ratio: 0.85; 95% confidence interval: 0.75 to 0.96) compared with radiotherapy alone 13 . Thus, based on those data and equipoise on optimal treatment, a shift from open surgery toward multimodality approaches for organ preservation has occurred in hpc despite the greater risk of acute and potentially chronic toxicities from concomitant chemotherapy 14,15 .Consistent with other population-based series, Hall observed an increase in the prevalence of concurrent chemoradiation in the post-2000 era and a decrease in the use of primary surgery or radiation alone, with no statistically significant difference in overall survival between the treatment groups 1,2 . Hall's main finding is the lack of a survival increment over the 20-year study period, leading to the conclusion that the addition of concomitant chemotherapy to definitive radiotherapy did not yield survival gains 1 .…”
mentioning
confidence: 99%
“…The Meta-Analysis of Chemotherapy in Head and Neck Cancer collaborative group, in a subgroup analysis of 2767 hpc patients, found a 5-year absolute survival improvement of 4% associated with concomitant chemotherapy (hazard ratio: 0.85; 95% confidence interval: 0.75 to 0.96) compared with radiotherapy alone 13 . Thus, based on those data and equipoise on optimal treatment, a shift from open surgery toward multimodality approaches for organ preservation has occurred in hpc despite the greater risk of acute and potentially chronic toxicities from concomitant chemotherapy 14,15 .…”
mentioning
confidence: 99%